Load transient between conventional diesel operation and low-temperature combustion. (June 2015) - Sarangi, Asish K; Garner, Colin P; McTaggart-Cowan, Gordon P; Davy, Martin H; Wahab, Emad; Peckham, Mark
The operation of diesel low-temperature combustion engines is currently limited to low-load and medium-load conditions. Mode transitions between diesel low-temperature combustion and conventional diesel operation and between conventional diesel operation and diesel low-temperature combustion are therefore necessary to meet typical legislated driving-cycle load requirements, e.g. those of the New European Driving Cycle. Owing to the markedly different response timescales of the engine's turbocharger, exhaust gas recirculation and fuelling systems, these combustion mode transitions are typically characterised by increased pollutant emissions. In the present paper, the transition from conventional diesel operation to diesel low-temperature combustion in a decreasing-load transient is considered. The results of an experimental study on a 0.51 l single-cylinder high-speed diesel engine are reported in a series of steady-state 'pseudo-transient' operating conditions, each pseudo-transient test point being representative of an individual cycle condition from within a mode transition as predicted by the combination of real-world transient test data (for fuelling and load) and one-dimensional transient simulations (for intake manifold pressure and exhaust gas recirculation rate). These test conditions are then established on the engine using independently controllable exhaust gas recirculation and boost systems. The results show for the first time that the intermediate cycle conditions encountered during combustion mode change driven by the load transient pose a significant operating challenge, particularly with respect to control of carbon monoxide, total hydrocarbon and smoke emissions. A split-fuel-injection strategy is found to be effective in mitigating the negative effects of the mode change on smoke emissions without significantly increasing oxides of nitrogen or decreasing fuel economy; however, unburned hydrocarbon emissions are increased. Additional experimental testing was also conducted at selected intermediate cycles to understand the sensitivity of key fuel injection parameters with the split-injection strategy on engine performance and emissions.